Análisis del cumplimiento del Artículo 65.- Clasificación de Audiencias y Franjas Horarias, en su literal “a. Familiar” (06:00 a 18:00); de la Ley Orgánica de Comunicación del Ecuador, en los medios de comunicación de televisión Ecuador TV y RTS. Periodo de investigación: septiembre, 2023. - Atiencie Valarezo, Gina Madelayne (2024)
Television content broadcast on television channels worldwide is governed by a legal framework that determines a classification of audiences and time slots, according to the age and content of the programming. This research work focused on analyzing Article 65 of the Organic Law of Communication of Ecuador, which deals with the classification of audiences and time slots, which at the time of its approval generated debate and controversy over its content, form, structure and application at the national level. Among the objectives of this research we sought to know the main problems that exist within the Ecuadorian television in its family time slot, highlighting the television contents that violate the provisions of the Organic Law of Communication. At the methodological level, the study focused on the application of an observation form, through which information was collected on the contents transmitted on Ecuador TV and RTS; similarly, a semi-structured interview was used to determine the opinion of experts with the profile of lawyers/communicators on whether or not these channels are complying with the provisions of the Law. The access to the analysis of the Ecuadorian television channels: Ecuador TV and RTS, showed that Ecuador TV complies with the provisions of the article, while RTS does not comply, especially with the programming that is broadcast at times defined for underage viewers. It can be concluded that this is because Ecuador TV is a State television channel, therefore, the rules that govern it are those of public television, while RTV, being a private channel, must opt for programming with content aimed at increasing audiences. Keywords: time slot; audience; television; television content; LOC (Organic Law of Communication).